Lessons learnt from the 2014 West Africa ebola viral disease (EVD) outbreak: economic, political and social impacts of disease outbreaks - Maingi, Nicodemus Nzoka; Matilu, Mwau Prof.; Ateya, Ismail Prof. (Strathmore University, 2018)
In many disease outbreaks, their effects can invariably be measured in both direct and indirect terms; directly by observable, measurable outcomes and indirectly by looking for knock-on effects post the disease outbreak. Some of these angles and degrees of measure could matter more and provide a different yet more objective measure of a true disease outbreak’s impact. Such measures include the economic, social and political implications following a disease outbreak. This research looks to study and document the economic, social and political implications of the 2014 West African EVD outbreak that mainly ravaged Guinea, Liberia and Sierra Leone. Whilst the outbreak may have been theoretically localized around the three countries, other neighboring and far flung but somewhat affiliated nations also had their share of the outbreak’s implications. This research also looks to study and identify knock-on effects of the outbreak in the other countries (outside the three at the outbreak’s epicenter). The research looks to inform and boost the focus on early and targeted mitigation efforts if only to safeguard the interests of regional blocks and other nations that may be victims of negative downturns as a result of such disease outbreaks. The research hopes to inform and spur intraregional and inter-national discussions and engagements on how to best deal with such disease outbreak in a measurable and sustainable manner, with an aim to possibly safeguard their socio-economic and political interests.
Keywords: Case Fatality Ratio; CFR; Centre for Disease Control and Prevention; CDC; Disease Surveillance Response Unit; DSRU; Ebola Virus Disease; EVD; Viral Hemorrhagic Fever; World Health Organization